Liver failure assessment associated with polinosa morbillarum - Usachova, E. V.; Smyrnova, Daria; Усачова, Олена Віталіївна (Запорізький державний медичний університет, 2018)
Since the beginning of 2017 Ukraine has reported more than 2,5 thousand confirmed measles cases included 4 deaths. Research data were collected on the clinical base Zaporizhzhya Infectious Disease Hospital. During measles patients monitoring were observed clinical features of liver failure including hepatomegaly and high activity of hepatic enzymes. The aim wasto establishedconnection between liver lesion and virus affect in measles patients. Materials and methods: 75 clinical cases were retrospectively analyzed. Patients were admitted to the hospital between September-December 2017. All collected data were processed by standard statistical procedures. Results:two groups were distinguished based on activity of alanine aminotransferase (ALT). Group 1 (with laboratory approved hepatic involvement) – includes 50,67% (38/75) patients. Group 2 –control with 49,33% (37/75) patients.
Keywords: тези доповідей